Investigation of The Effects of BD35 (Biodiesel/Diesel Blend) and Propanol Usage in Combustion Characteristics in A Dual Fuel Diesel Engine - Okcu, Mutlu; Fırat, Müjdat; Varol, Yasin (My University, 2024)
This study investigates the changes in the combustion characteristics of a diesel engine modified to operate in reactivity controlled compression ignition mode using propanol as low reactivity fuel and BD35 as high reactivity fuel. In the study, BD35 fuel, a blend of 35% biodiesel and 65% petroleum-derived diesel, was sprayed directly into the cylinder as a high reactivity fuel, while propanol was sprayed into the intake manifold at low pressure as a low reactivity fuel for reactivity controlled compression ignition. Four different low reactivity fuel premixed ratios of 0%, 15%, 30% and 45% propanol were used in the experiments. The experiments were carried out under 60% engine load and 2400 (rpm) constant engine speed conditions. According to the data obtained, it was found that the maximum in-cylinder pressure value increased with the increase in the premixed ratio and a significant increase occurred especially when 45% premixed ratio was used. Although the use of propanol as low reactivity fuel in the test engine under the reactivity controlled compression ignition concept was observed to cause a decrease in the indicated mean effective pressure, the rate of decrease in the indicated mean effective pressure was found to slow down as the premixed ratio increased. Finally, it was found that the in-cylinder gas temperature decreased significantly with increasing the propanol premixed ratio. When all the findings are analyzed, it has shown an important way to understand the effects of propanol as low reactivity fuel and BD35 as high reactivity fuel on engine performance at high load in diesel engines modified to operate in reactivity controlled compression ignition mode.
Keywords: Combustion; Biodiesel; RCCI; Propanol; BD35